Utilization Of Biogas As An Effort To Mitigate & Adapt To Climate Change In Indonesia - Mohd Abi Rafdi; Imelda Chaerani Surnati (Jurnal Indonesia Sosial Teknologi, 2022)
The preparation of this paper is a form of implementation related to the paper entitled Navigating Amid Uncertainty in Spatial Planning by Zandvoort, M., and friends in 2017. The paper contains the form of uncertainty faced by planners in the planning process. Uncertainty is divided into 3 types, namely ontic uncertainty which does not know a phenomenon to a certain degree, while epistemic uncertainty is a phenomenon that can be known to a certain level, and ambiguity uncertainty is knowledge and different perceptions of a phenomenon. One form of uncertainty that occurs in planning is climate change. The phenomenon of climate change is a phenomenon caused by human activities either directly or indirectly. This activity triggers changes in the composition of gases in the atmosphere within a certain time. The countermeasures are in the form of mitigation and adaptation measures. One form of climate change mitigation and adaptation is the utilization of biogas. Biogas is a gas that comes from anaerobic activity (fermentation) from organic materials such as animal manure. The state of Indonesia has a large number of livestock and of course, produces manure. If left unchecked it will become pollution. For that, it needs processing to become something useful. Biogas has benefits as a new energy that can be utilized. Besides that, biogas can fight the greenhouse effect, which triggers climate change. In Indonesia, not all provinces where people process livestock manure into biogas for daily use.